Efforts to Improve Road Safety on Teuku Umar Bekasi - Wisudawanto, Feri; Hutabarat, Torang; Cahyani, Penni (Dinasti International Journal of Digital Business Management, 2025)
Road safety is a crucial issue in developing Indonesia's transportation infrastructure. Jalan Teuku Umar in Tambun, Bekasi, is one of the primary routes connecting Bekasi with neighboring areas, yet it experiences a high rate of traffic accidents. Accidents on this road, driven by user behavior, inadequate road conditions, and frequent traffic violations, lead to significant material losses and, in some cases, severe injuries or fatalities (Salvapour et al., 2020). This study aims to analyze factors contributing to the high accident rate on Jalan Teuku Umar and proposes measures to enhance traffic safety. Previous research highlights driver behavior as a primary cause of accidents, with frequent violations such as red light running, speeding, and lack of attention to pedestrians (Moshki et al., 2019; Sullman et al., 2012). Additionally, infrastructure issues, including inadequate pedestrian facilities and irregular traffic flow, further compromise road safety (Demiroz et al., 2015). This research focuses on identifying risk factors specific to Jalan Teuku Umar and recommends solutions to mitigate accidents and improve safety. The study employs a quantitative, descriptive approach, incorporating field observations, surveys, and accident data analysis. A survey was conducted with 200 respondents, including drivers and pedestrians, to assess traffic behavior and safety awareness. Secondary data from police reports over three years provided insight into accident patterns and dominant causes (Sullman et al., 2012). Descriptive analysis of the collected data highlights the correlation between safety awareness, road conditions, and accident frequency. Key findings indicate that traffic violations, limited geometry road capacity, the dominance of motorcycles, inadequate road use, and the impact of land use all significantly contribute to the high accident rate. Traffic violations, helmet particularly non-use, unlit headlights, and seatbelt neglect, account for most accidents, aligning with similar findings in other areas (Kurniastuti et al., 2021). Motorcycles dominate the traffic flow, increasing fatal accident risks due to low helmet use. High-density commercial activities also create complex traffic interactions. Recommendations include stricter law enforcement on violations, infrastructure improvements, road capacity expansion, and educational campaigns on traffic safety. Regular road geometry maintenance, improved signage, and better land use management are essential to reduce accidents on Jalan Teuku Umar. This study contributes to policy development for enhancing road safety in Bekasi and similar urban areas by providing a comprehensive analysis of risk factors and proposing targeted interventions.